2015
DOI: 10.1108/ijebr-06-2014-0100
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the family effect on firm performance

Abstract: Purpose – The purpose of this paper is to investigate how internal social capital – as a part of the familiness resources– affects family firm performance. The social capital theory states that internal social capital within family businesses is composed of three dimensions: the structural dimension, the relational dimension, and the cognitive dimension. The aim of the paper is to study the relationship between each dimension of internal social capital and family firm performance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 80 publications
1
23
0
Order By: Relevance
“…The studies highlighted the consequences of bonding SC, bridging SC, and family SC. Bonding SC was found to positively affect firm performance (Campbell & Park, 2016; Herrero, 2018; Y. Mani & Lakhal, 2015; Tasavori et al, 2018).…”
Section: Social Capital In Family Firms: the Findingsmentioning
confidence: 95%
See 3 more Smart Citations
“…The studies highlighted the consequences of bonding SC, bridging SC, and family SC. Bonding SC was found to positively affect firm performance (Campbell & Park, 2016; Herrero, 2018; Y. Mani & Lakhal, 2015; Tasavori et al, 2018).…”
Section: Social Capital In Family Firms: the Findingsmentioning
confidence: 95%
“…The ISC-FB construct was also used by Tasavori et al (2018) and Y. Mani and Lakhal (2015), who, however, treated the three first-order constructs of Carr et al (2011) as separate.…”
Section: Definitional and Measurement Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…From a family firm resource view (Sirmon and Hitt 2003;Uhlaner et al 2013), it is argued that under conditions of limited financial resources, family firms will focus on innovation strategies with a short-term return horizon instead of disruptive innovation strategies that require a long-term return horizon (Sharma and Salvato 2011; Singh and Gaur 2013). Furthermore, family firms possess the social capital to react quickly to innovation opportunities and to tolerate a degree of risk in doing so, which creates an advantage for disruptive innovation activities (Mani and Lakhal 2015;Zahra 2003). However, other studies have found that family social capital might also cause a limited perspective that prevents new resources and novel information, which are essential for adopting disruptive innovations, from entering the family firm (Herrero and Hughes 2019).…”
Section: Disruptive Innovation and The Family Firmmentioning
confidence: 99%